Indoor-type photovoltaics with organic solar cells through optimal design. (December 2018) - Vincent, Premkumar; Shin, Sang-Chul; Goo, Ji Soo; You, Young-Jun; Cho, Boram; Lee, Suwoong; Lee, Dong-Wook; Kwon, Se Ra; Chung, Kwun-Bum; Lee, Jae-Joon; Bae, Jin-Hyuk; Shim, Jae Won; et al.
Abstract: Indoor solar cells are an attractive option to install in buildings to harvest the energy emitted by indoor lighting. They can be implemented as a stand-alone grid, or as part of an integrated energy harvesting unit. Previous research has utilized amorphous silicon and dye-sensitized solar cells for power generation from a fluorescent light source. In our study, we evaluated the applicability of a poly (3-hexylthiophene):indene-C60 bisadduct solar cell to harvest the light spectrum from an indoor light-emitting diode (LED). Because the absorption peak of poly (3-hexylthiophene) overlaps the LED spectrum peak, it serves as a good candidate for indoor light harvesting under an LED source. We have extracted the power conversion efficiency of the solar cell under different LED illuminance values, such as 200, 800, 1000, and 2000 lx. With the help of finite-difference time domain simulations, we optimized the solar device structure for each illuminance. The results detailed in this article were intended to assess the applicability of organic solar cells as indoor photovoltaics, and to provide a methodology to optimize the photovoltaic structure to maximize its efficiency.